Perlindungan Hukum Bagi Investor Dalam Transaksi Cryptocurrency Pada Aplikasi Binance Di Indonesia - Widianti, Ira Ayu; Hardian Iskandar (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
The development of crypto in Indonesia currently has a high attraction for the public. Indonesia is one of the countries that has quite good crypto investors and has great investors. With this crypto transaction, it adds investment for life, but many companies engaged in this crypto sector are still vulnerable to the establishment of Bappebti or the number of illegal companies. So that legal protection cannot be obtained on crypto companies that do not have permits. One of them, the Binance application (currently) still has not obtained permission from Bappebti. The type of research in this article is literature research with a qualitative approach. The methodology used is the normative study of law. The results of the study concluded that there is no fixed legal certainty for Binance application users for investors, because the company has not registered with Bappebti to legalize its crypto in Indonesia